A sustentabilidade da carcinicultura no município de Fortim-CE, com ênfase nos aspectos sociais, ambientais e tecnológicos - Joventino, Fatima Karine Pinto (2006)
This dissertation analyzes the sustainability of the carcinoculture in the city of Fortim- Ceará, taking into consideration environmental, social and technological aspects. The research aimed at identifying the main handling practices and the technology that has been adopted in the shrimp culture farms, and its contribution to a sustainable development of the activity. The study presents some forms of technology and handling practices that can be adopted by the farms, which are considered less environmentally impacting, and it also identifies the main impacts generated by the activity. Primary and secondary data were used. The primary data were obtained by means of an empirical research carried out in the city of Fortim, during the months of April and August, 2005. During these visits, questionnaires were applied, with semi-structured and open questions. It was also possible to carry out interviews with representatives of governmental agencies and the business community. Secondary data were obtained by means of bibliographical research comprising theses, books and articles on the issue, as well as documents such as reports, Codes of Conduct, Federal and State government directives, and assessments made by governmental agencies in charge of regulating and supervising the activity. In this study, tabular and descriptive analysis techniques and a modified version of the “Forest Service of United States Agricultural Department (1986) methodology were applied. These methods made it possible to transform the qualitative variables into quantitative ones, through numerical values and weights so as to obtain a Significance Index of the technological, environmental and social variables. Upon the results obtained by these Indexes, it was possible to assess that the carcinoculture in the region is not developing on a sustainable basis, rejecting, therefore, the proposed hypothesis, according to which the handling practices and the technology that has been used in these farms are contributing for the development of the activity in a way that is in harmony with the environment. In spite of the existence of some initiatives that suggest that the sector is starting to take into consideration environmental matters, it is possible to affirm that the actions carried out by the sector’s main entities have not been able to effectively promote the necessary changes in the behavior and conduct of the business, neither has it been able to call the attention to the importance of preserving the environment.